Parenting practices, children’s lifestyle behaviours and childhood obesity - Brown, J; Nicholson, J; Broom, D (My University, 2011)
The impact of children’s individual lifestyle behaviours on obesity is well known. But these behaviours are shaped by the child’s economic and social environment. Of particular importance is the child’s home environment characterised more broadly by such things as household income, parental well-being and behaviours – all of which may determine specific activity and dietary patterns. Data from the first three waves of the Longitudinal Study of Australian Children (LSAC) was used to investigate whether children’s lifestyle behaviours (Wave 2, child aged 6/7) mediate the relationship between distal household/family variables (Wave 1, child aged 4/5) and child weight status (Wave 3, child aged 8/9). Results from the structural equation model revealed associations between the cluster of household and parental characteristics at Wave 1 (household income and mother’s psychological distress, weight status and consistent parenting behaviour) with the cluster of lifestyle behaviours at Wave 2 (time spent watching television and engaging in moderate to vigorous exercise and snacking) and child weight status when the children were aged 8/9 years. More specifically the model revealed a clear pathway linking household income, mothers parenting behaviour, television viewing and child weight status.
Keywords: Activities -- Children's activities; Health -- Physical activity; Child Development -- Physical; Childhood and child development; Health and wellbeing; Child Development; Health; Activities; Physical activity; Physical; Children's activities; Childhood and child development; Health and wellbeing